A curious observation of phenomena occurring during lapping/polishing processes. (31st October 2019) - Yang, Yue; Li, Haonan; Liao, Zhirong; Axinte, Dragos
Abstract : We demonstrate that the kinematics of the polishing process is more intriguing than an idealized planetary movement as all the previous studies reported. In reality, the workpiece is pseudo-constrained by the planetary carrier and because of this its relative motion to the polishing pad also incurs a 'parasitic' movement that previously has not been observed. Here, we report and model this parasitic movement and quantify its effect upon the workpiece surface roughness. Using a motion capture system, the principal and 'parasitic' movements between the sample and polishing tool have been tracked and our models validated. It is proved that considering this parasitic movement the prediction of workpiece surface morphology can be significantly improved when compared with the idealized approach (i.e. planetary). Our observations and modelling framework open the avenue to carefully consider the compliance between the tools and workpiece in other manufacturing processes for accurate predictions of the process outcomes.